Characterizing ZSV of SBS modified asphalt using shear rate sweep test and frequency sweep oscillation test. (31st March 2023) - Zhang, Jiakang; Luo, Ting; Cui, Yong; Xie, Bin; Wang, Jiaxin; Yan, Chuanqi
Highlights: ZSV was characterized using both shear rate sweep test and frequency sweep test. The cox-merz rule is valid for plain asphalt but not for SBSMA, especially highly modified ones. SBSMA must be pure viscous (δ = 90°) to obtain a strict η* plateau. A pseudo-plateau for η* was observed in the master curve. Abstract: The Zero-shear viscosity (ZSV) of asphalt is frequently measured using shear rate sweep test (η) or frequency sweep test (η*), whose correlation is often established via the cox-merz rule. However, the applicability of cox-merz rule upon SBS modified asphalt (SBSMA) is still debatable. This study aims to characterize ZSV of SBSMA using both shear rate sweep test and frequency sweep test and examine the cox-merz rule for SBSMAs with different SBS contents. The testing temperature is fixed at 60 °C and to enlarge the η* testing frequency range, master curve is created based on a novel double sigmoidal model. Results indicate that cox-merz rule is valid for plain asphalt but not for SBSMA, and the deviation is more evident for highly modified SBSMA (the deviation increases from 0.8 % to 13.2 %). Based on Kramers-Kronig relations, SBSMA must be pure viscous (phase angle δ = 90°) to obtain a strict η* plateau for ZSV measurement, which is quite difficult because SBSMA can only be pure viscous above the SBS polymer glass transition temperature (100 °C). Therefore, it is theoretically impossible to obtain an SBSMA η* plateau at 60 °C that resembles the η plateau, hence the cox-merz rule fails. A η* Newtonian plateau was observed in the master curve, but it was obtained at temperatures higher than 100 °C and cannot be used for 60 °C ZSV measurement either. With reduced frequency, the η* master curve of SBSMA shows 4 stages including a "pseudo-plateau". The pseudo-plateau should be treated with care and cannot be used for ZSV measurement.